2013
DOI: 10.1128/iai.01033-12
|View full text |Cite
|
Sign up to set email alerts
|

Site of Isolation Determines Biofilm Formation and Virulence Phenotypes of Streptococcus pneumoniae Serotype 3 Clinical Isolates

Abstract: Streptococcus pneumoniae is a diverse species causing invasive as well as localized infections that result in massive global morbidity and mortality. Strains vary markedly in pathogenic potential, but the molecular basis is obscured by the diversity and plasticity of the pneumococcal genome. In the present study, S. pneumoniae serotype 3 blood (n ‫؍‬ 12) or ear (n ‫؍‬ 13) isolates were multilocus sequence typed (MLST) and assessed for biofilm formation and virulence phenotype. Blood and ear isolates exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…However, in the present study, we not only observed highly significant differences in virulence and pathogenic profiles between isolates belonging to the same serotype and clonal lineage but also found a close correlation between pathogenic profiles in mice and the original sites of isolation from human cases of pneumococcal disease. This extends an observation that we have previously reported for serotype 3 strains belonging to ST180, ST232, and ST233 (8). Thus, stable niche adaptation within a clonal lineage appears to be a general phenomenon.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…However, in the present study, we not only observed highly significant differences in virulence and pathogenic profiles between isolates belonging to the same serotype and clonal lineage but also found a close correlation between pathogenic profiles in mice and the original sites of isolation from human cases of pneumococcal disease. This extends an observation that we have previously reported for serotype 3 strains belonging to ST180, ST232, and ST233 (8). Thus, stable niche adaptation within a clonal lineage appears to be a general phenomenon.…”
Section: Discussionsupporting
confidence: 74%
“…The plethora of capsular serotypes and clonal lineages (MLST types) no doubt contribute to their adaptability in different host microenvironments, but they have also complicated previous attempts to unequivocally associate particular serotypes or clonal groups with specific virulence attributes (6, 7). However, we have previously described multiple examples of serotype 3 strains belonging to the same ST that consistently and reproducibly exhibit distinct virulence phenotypes in mice that directly correlate with the original site of isolation from human patients (i.e., ear versus blood) (8). This suggested that, at least in serotype 3, pneumococci exhibit stable niche adaptation within a clonal lineage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations